Representasi Peran Ayah Domestik: Kajian Semiotika Roland Barthes pada Film Dua Hati Biru - Wijaya, Calvin; Winduwati, Septia (Kiwari, 2025)
Many films present the family drama genre to provide implicit or written messages aimed at knowledge or understanding about the family. The role of the father is one of the important roles in the family because in Indonesian culture the role of the father is considered the mainstay of the family who is responsible for finances and emotions. One of the films is the film Dua Hati Biru which presents a story about a family with the main character named Bima as a father. By using the theoretical basis and concepts of semiotics, representation, the role of domestic fathers, mass communication, and the concept of gender in Indonesian culture. The method used is semiotic analysis by using the researcher, namely Roland Bathes' semiotic theory (Denotation, Connotation, and Myth) which is descriptive with a qualitative approach, this study aims to describe the role of the father in the film Dua Hati Biru. The results of this research are the role of the father in the film Dua Hati Biru as a protective figure, fathering, responsible for the moral and emotional education of children, problems or conflicts in his family, and never giving up trying to meet the family's needs. Banyak film yang menyajikan genre drama keluarga untuk memberikan pesan tersirat maupun tertulis bertujuan sebagai pengetahuan atau pemahaman mengenai keluarga. Peran ayah merupakan salah satu peran penting dalam keluarga karena dalam budaya di Indonesia peran ayah dianggap sebagai tumpuan utama keluarga yang bertanggung jawab atas finansial dan emosional. Salah satu filmnya adalah Film Dua Hati Biru yang menyajikan cerita tentang keluarga dengan karakter utama bernama Bima sebagai seorang Ayah. Dengan menggunakan menggunakan landasan teori dan konsep dari semiotika, representasi, peran ayah domestik, komunikasi massa, dan konsep gender di budaya Indonesia. Metode yang digunakan analisis semiotika dengan menggunakan peneliti yaitu teori semiotika Roland Barthes (Denotasi, Konotasi, dan Mitos) yang bersifat deskriptif dengan pendekatan kualitatif, penelitian ini bertujuan untuk mendeskripsikan peran ayah dalam film Dua Hati Biru. Hasil penelitian ini adalah adanya peran ayah dalam film Dua Hati Biru sebagai protective figure, mengasuh anak, bertanggung jawab atas pendidikan moral dan emosional anak, masalah atau konflik yang ada di keluarganya, dan tidak pantang menyerah berusaha memenuhi nafkah keluarga.